2018
DOI: 10.3758/s13421-018-0879-4
|View full text |Cite
|
Sign up to set email alerts
|

Auditory distraction does more than disrupt rehearsal processes in children’s serial recall

Abstract: As children mature, their ability to remember information improves. This improvement has been linked to changes in verbal control processes such as rehearsal. Rehearsal processes are thought to undergo a quantitative shift around 7 years of age; however, direct measurement of rehearsal is difficult. We investigated a measure of rehearsal ability in children and compared this measurement to serial recall performance in the presence of auditory distractors. Theories of auditory distraction effects in children re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…This is nevertheless an interesting aspect for future research for the following reasons: First, quiet, distraction-free phases often occur in everyday situations in which one cannot necessarily predict whether or when auditory distraction might appear. Second, recent evidence suggests that—contrary to previous assumptions [e.g., 10 , 22 ]—there is noteworthy disruption of serial recall when comparing a steady-state condition (used here as a baseline for determining the auditory-deviant and the changing-state effect) with a quiet condition [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 71%
“…This is nevertheless an interesting aspect for future research for the following reasons: First, quiet, distraction-free phases often occur in everyday situations in which one cannot necessarily predict whether or when auditory distraction might appear. Second, recent evidence suggests that—contrary to previous assumptions [e.g., 10 , 22 ]—there is noteworthy disruption of serial recall when comparing a steady-state condition (used here as a baseline for determining the auditory-deviant and the changing-state effect) with a quiet condition [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 71%
“…Respective studies with adults found no evidence for an association between short-term memory capacity and the ISE (Ellermeier & Zimmer, 1997;Elliott & Cowan, 2005, Exp,1;Elliott et al, 2020), with the exception of Elliott and Cowan (2005, Exp. 2), who reported a significant correlation. Following these studies, we used serial recall performance in quiet as an estimate of individual short-term memory capacity, and difference scores (performance in quiet -performance with changing-state speech) as a measure of ISE (AuBuchon et al, 2019;Ellermeier & Zimmer, 1997). Both measures were normally distributed in children and adults.…”
Section: Verbal Taskmentioning
confidence: 99%
“…In a series of studies, Hughes et al (2005Hughes et al ( , 2007Hughes et al ( , 2013 provided evidence for the duplex-mechanism account by confirming the predicted dissociation between the auditory deviation effect and the CSE. In these studies, the CSE is considered instead of the ISE, since the latter may result from the combined action of both mechanisms, i.e., a steady-state effect indexing attention capture (Bell et al, 2019b), and a changing-state effect indexing interference-by-process (AuBuchon et al, 2019). The findings revealed independent, additive effects of changing-state speech and unexpected voice deviants on verbal serial recall performance (Hughes et al, 2007), as well as differential effects of moderating variables: The CSE, but not the deviation effect, was confined to a task requiring serial order retention (Hughes et al, 2007), whereas the deviation effect, but not the CSE, was confined to the encoding phase of the task and was moderated by manipulations of the participants' attention control, i.e., by providing warnings on the upcoming irrelevant sound, by focal task engagement, and by individual working memory capacity (WMC) (Hughes et al, 2013;Sörqvist, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the current dual task manipulations revealed rehearsal-not attentional refreshing-was the dominant strategy used by adults in both forward and backward serial recall. Importantly, rehearsal may require more controlled attentional resources for school-age children than adults (AuBuchon, McGill, & Elliott, 2019). Thus, measures of immediate serial recall performance in early childhood may have a predictive value for long-term outcomes precisely because rehearsal has not become automatic.…”
Section: Resultsmentioning
confidence: 99%